English Language Education Across Greater China 2011
DOI: 10.21832/9781847693518-015
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 13. Learning English as a Third Language by Uyghur Students in Xinjiang: A Blessing in Disguise?

Abstract: The spread and rapid rise in status of English language in education and society across China in recent years has been widely discussed and debated by scholars as well as policy makers. More recently, the phenomena described as "English and Chinese bilingual education" has been promoted and gained currency in educational establishments in economically developed costal regions and urban centres in the country, with the ostensible aim of achieving both language proficiency and subject learning simultaneously. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In contrast, the Uyghur students interviewed showed little or no motivation to learn Mandarin, despite its potential linguistic capital, as they felt they were always at a disadvantage compared to Han students' whose mother tongue was Mandarin. Given that multilingualism is now considered to be a major source of funds of knowledge (Wei, 2014), Sunuodula and Feng's (2011) results suggest that in some contexts in China English may be a more effective source of funds of knowledge than Mandarin. However, it has been noted that identity texts can lead to knowledge reproduction rather than knowledge production (Subero et al, 2016).…”
Section: Identity Textsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the Uyghur students interviewed showed little or no motivation to learn Mandarin, despite its potential linguistic capital, as they felt they were always at a disadvantage compared to Han students' whose mother tongue was Mandarin. Given that multilingualism is now considered to be a major source of funds of knowledge (Wei, 2014), Sunuodula and Feng's (2011) results suggest that in some contexts in China English may be a more effective source of funds of knowledge than Mandarin. However, it has been noted that identity texts can lead to knowledge reproduction rather than knowledge production (Subero et al, 2016).…”
Section: Identity Textsmentioning
confidence: 99%
“…Identity texts could provide teachers with an effective strategy for drawing on, and valorising, minority languages and identities, which could then be used to scaffold the development of socially just literacy. For example, Sunuodula and Feng (2011) found that despite having few opportunities to learn their mother tongue, Uyghur university students were nevertheless still highly motivated to learn English as they perceived it as a form of linguistic capital with which they could compete with Han students. In contrast, the Uyghur students interviewed showed little or no motivation to learn Mandarin, despite its potential linguistic capital, as they felt they were always at a disadvantage compared to Han students' whose mother tongue was Mandarin.…”
Section: Identity Textsmentioning
confidence: 99%
“…This shift from bilingualism to trilingualism or multilingualism, we argue, is attributable to various forces of globalisation in the wider context which triggered the promulgation of the official documents (Ministry of Education 2001a, b, c); to promote English language education at all levels throughout the country. Some minority students at universities, who find themselves in difficulty competing academically with their Han counterparts, perceive the requirement to learn English as an opportunity to demonstrate their learning capabilities (Sunuodula and Feng 2011). Some minority students at universities, who find themselves in difficulty competing academically with their Han counterparts, perceive the requirement to learn English as an opportunity to demonstrate their learning capabilities (Sunuodula and Feng 2011).…”
Section: Complexity Of the Contextmentioning
confidence: 99%
“…This would actually signify setting standards for English language proficiency lower than the required levels specified in official documents issued by the Ministry of Education (2001a, b, c). Sunuodula and Feng (2011) point out that those making this suggestion seem to ignore the obvious consequences that, once such a special policy is made, minority pupils with lower standards than their majority counterparts in a school subject of ever-increasing importance will inevitably find it more difficult to compete for academic and career opportunities, and will be destined to be further marginalised.…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation